Under Control Governance Across the Enterprise - Lamm, Jacob; Blount, Sumner; Boston, Steve; Camm, Marc.; Cirabisi, Robert; Cooper, Nancy E.; Datskovsky, Galina; Fox, Christopher; Handal, Kenneth V.; McCracken, William E.; Meyer, John.; Scheil, Helge; et al. (Berkeley, CA : Apress, 2010)
With the economic crisis that began in 2008, a long-standing trend toward increased regulation is becoming a flood. The clamor for improved enterprise risk management and the complexity of multinational compliance present executives with a dramatically new array of challenges. Governance should offer solutions, but it is clear that yesterday$1 (Bs governance practices aren$1 (Bt up to the task. In both design and implementation, they are too disconnected and incomplete to fully address our complex compliance and risk management puzzle. Executives get only fragmented views of their true business performance, and inefficiencies drive up costs. The consequences of inadequate governance were demonstrated in the economic meltdown of 2008. As the world struggles to recover from that crisis, business is now faced with a confusing array of evolving regulations, the challenge of managing compliance across multinational organizations and a new imperative for risk management that is coordinated across the enterprise. It$1 (Bs clear that yesterday$1 (Bs governance practices don$1 (Bt meet today$1 (Bs need for centralized controls, integrated compliance and risk management and greater transparency. The need for organizations to change$1 (Band change now$1 (Bis clear. Under Control captures decades of business governance experience from many of the leading authorities at CA, Inc. This book sets out not only to explain the essential challenges of effective business governance, but to help you build solutions for your organization based on lessons learned at CA from its customers and in its own corporate structure. From governing the organization$1 (Bs policies as a whole instead of in silos, to a department-by-department look at the role and impact of governance, to governing your green initiatives, to the role of the board of directors, to the importance of risk management, this book lays out some of the strategies and processes that may help your organization manage its risk and regulatory requirements. It is clear that the governance standards in the past were inadequate, and that risks have not been properly assessed or understood. This book is a first step in solving this problem so that your organization is prepared and able to respond and thrive in today$1 (Bs rapidly evolving environment. Under Control is the first book published in the new CAPress imprint, a joint publishing program between Apress and CA Inc. (3z(BOne of the defining factors of the first decade of the 21st century has been the increase of regulation and governance. To explain these trends, and the various best practices for ensuring governance, enterprise IT management solutions provider CA Inc. enlisted more than a dozen subject matter experts from its ranks to contribute content. The resulting book explores the need for broad governance, different areas where governance is important, and various ways for organizations to manage and implement compliance, including IT governance, project portfolio management, information governance and sustainability management. The book, while largely vendor-neutral, draws on CA's experience creating governance solutions as well as managing its own governance issues.(3y $1 (BAaron Smith, Projects@Works
The Rise of Governance -- Governance Today -- Policy Management -- Risk Management -- Risk Governance and the Board of Directors -- Governance of Risk and Compliance -- IT Governance, Risk, and Compliance -- Governance and Portfolio Management -- The Regulatory Environment -- Governance and Finance -- Information Governance -- Governance and Sustainability.
Keywords: Computer science; Computer Science; Programming Techniques